Bacteriological Status of Tuberculosis Cases and Tuberculosis Symptoms in HIV Infected Persons in Kathmandu - Dhungana, GP; Ghimire, P; Sharma, S; Rijal, BP (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background: Clinical presentations of Tuberculosis (TB) vary with in HIV positive and HIV negative individuals. Smear negative tuberculosis is the leading cause of death of HIV patients. Objective: To examine the relationship between bacteriological status of TB cases and TB symptoms in HIV patients. Methods: A cross-sectional analytical study was conducted during January 2004 and August 2005 in a representative sample of 100 HIV infected persons visiting different Voluntary Counseling and Testing Centers (VCT) and HIV/AIDS care centers located in Kathmandu. Laboratory investigation of Tuberculosis was done by AFB staining and culture in ogawa medium. Data obtained through pre structured questionnaire and laboratory investigation were entered into SPSS 11.5 and analyzed. Results: Twenty three percent prevalence of TB is observed in HIV patients. Eighty one percent of the total TB cases were smear negative cases. Significant relationship was observed between the TB symptoms and Smear positive TB cases (χ2 =4.01, p<0.05, at 1 degree of freedom) but no significant relationship could be established between TB symptoms and smear negative cases (χ2 =0.82, p>0.05, at 1 degree of freedom). Mycobacterium avium complex (40.9%) was predominant followed by M. tuberculosis (27.3%) Conclusion: In HIV patients, the utility of direct microscopy of AFB stained smear is limited because most of these patients were smear negative and are asymptomatic. So, direct microscopy in combination with Culture is recommended for higher case finding of TB in HIV patients. Key words: Asymptomatic; smear negative TB; HIV/AIDS; Kathmandu DOI: 10.3126/saarctb.v5i1.3077 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 7-12